Contribution of human esterases to the metabolism of selected drugs of abuse. Issue 1 (5th January 2015) - Meyer, Markus R.; Schütz, Aline; Maurer, Hans H.
Highlights Characterization of the enzyme-catalyzed ester hydrolysis of ten drugs including eight drugs of abuse. Investigation of different esterase sources and isoforms. Kinetic parameters (Vmax/Km) determined for each reaction. Presented data important for prediction of drug–drug or drug–food interactions as well as for individual variations in metabolism.